Multiple Intratesticular Cysts - Kang, Sung Min; Hwang, Dae Sung; Lee, Jung Woo; Chon, Won Hee; Park, Nam Cheol; Park, Hyun Jun (The world journal of men's health, 2013)
Intratesticular cysts, once thought to be a rarity, are now being reported with an increasing prevalence as a result of the wider use of scrotal ultrasound scanning. Despite greater understanding of intratesticular cysts, their management remains unclear. Treatment has included enucleation and even radical orchiectomy over fear of the possibility of an associated malignancy. A more conservative approach with serial ultrasound scanning has been advocated if a clear distinction can be made between neoplastic and non-neoplastic testicular cysts. However, in view of the benign nature of such cysts, even repeated ultrasound scanning may not be necessary and may be considered over-treatment. In this study we present clinical and morphological characteristics of multiple cysts in the right testicle in a 62-year-old patient, where a slightly nodular lesion in the right testicle was detected.